DIBH technique guided by an optical system in left breast irradiation. (September 2016) - Russo, S.; Rossi, F.; Paoletti, L.; Barca, R.; Fondelli, S.; Alpi, P.; Grilli, B.; Esposito, M.; Pini, S.; Ghirelli, A.; Cunti, L.; Isgrò, L.; et al.
Abstract : Introduction: Optical systems provide both patient setup verification and intrafraction motion detection and enable respiratory gating treatment procedure. Purpose: Aim of this work is the evaluation of a deep inspiration breath-hold (DIBH) technique guided by an advanced optical system in terms of dosimetric benefits and positional accuracy. Materials and methods: The CatalystTM (C-RAD Sweden) can manage respiratory gated treatments by enabling visualization of the respiratory pattern and direct beam control. Forty left side adjuvant radiotherapy patients were included in this study. Standard 3D conformal radiotherapy technique with tangential beams and 50 Gy dose prescription were used. For each patient a free breathing (FB) and a DIBH treatment plans were elaborated and dose volume histograms were compared. Treatments were performed in DIBH. Interfraction and intra-fraction variability were quantified in mean and SD translations and rotations displacements over all the treatment fractions. Results: A significant dose reduction in Heart Mean Dose (1, 3 Gy FB vs 0, 4 Gy BH), and LAD mean dose (10, 7 Gy FB vs 2, 0 Gy BH) was achieved by DIBH technique. DIBH plans provided a better PTV coverage (V 95% 88, 9% FB vs 92, 6% BH) and no difference in Lung V10, V20 and Dmean. Inter-fraction variability after setup correction was lower than 1 mm and 1° for translations and rotations respectively. Intra-fraction variability was < 2.1 mm in translations and < 1° in rotations. Conclusion: Significant reduction of hearth and LAD mean dose and a limited inter-fraction and intra-fraction variability were obtained by DIBH treatments guided by an optical system.